Cryogenic RF Material Testing with a High-Q Copper Cavity - Guo Jiquan; Tantawi, Sami; Martin, David; Yoneda, Charles (AIP conference proceedings, 2010)
An X-band RF cryogenic material testing system has been developed in the past few years. This system employs a high-Q copper cavity with an interchangeable flat bottom working under a TEsub 013 like mode. By measuring the cavity Qs with a network analyzer, the system can characterize the surface resistance of different samples at different temperatures. Using a 50 MW 2mus pulsed klystron, the system can measure the quenching H field for superconducting samples, up to 300-400 mT. In this paper, we will present the most recent developments of the system and testing results.